The impact of information exposure on husbands involvement in maternal emergency prevention - Alamsyah Alamsyah; Ruqaiyah Ruqaiyah; Tut Handayani; Nur Hamdani Nur (AcTion: Aceh Nutrition Journal, 2025)
Maternal emergencies remain one of the leading causes of maternal morbidity and mortality; therefore, preventive efforts through adequate nutritional management during pregnancy are of paramount importance. The husband’s role in supporting pregnant women, particularly by understanding and ensuring adherence to proper dietary practices, is crucial in reducing the risk of complications. This study aimed to analyze the effect of information exposure on husbands’ knowledge regarding maternal emergency prevention through dietary pattern management. A cross-sectional design was employed in April 2025, involving 399 husbands residing in Makassar City and Gowa District, selected using accidental sampling. Data were collected online using a structured questionnaire that assessed sources of information, frequency of exposure, accessibility, and activeness in seeking information. The chi-square test was applied for statistical analysis. The results revealed that information exposure had a significant effect on husbands’ knowledge (p < 0,0001), including aspects of information sources, frequency of exposure, accessibility, and activeness in seeking information. In conclusion, improving the quality and accessibility of nutritional information for husbands plays an essential role in supporting maternal emergency prevention through the optimization of dietary patterns during pregnancy.